ENDOGENOUS ENDOPHTHALMITIS IN THE SETTING OF COVID-19 INFECTION: A Case Series. Issue 8 (August 2021) - Bilgic, Alper; Sudhalkar, Aditya; Gonzalez-Cortes, Jesus H.; March de Ribot, Francesc; Yogi, Rohit; Kodjikian, Laurent; Mathis, Thibaud
Abstract : Purpose: To describe endogenous endophthalmitis in the setting of COVID-19 pneumonia. Methods: Patients recovering from COVID-19 pneumonia who presented to our department with any or all of the following complaints: pain, watering, redness, and decreased vision were identified. All relevant data were collected for analysis. Results: Three patients with endogenous endophthalmitis were identified. All patients had been treated for COVID-19 pneumonia and therefore had received remdesivir and systemic steroids; 2 of the 3 patients received tocilizumab. All patients received vitreous biopsy, vitrectomy, and intraocular antibiotic injection. Patient 1 demonstrated Klebsiella pneumoniae in blood culture, K. pneumoniae and Escherichia coli in urine culture, and K. pneumoniae in vitreous fluid, whereas Patients 2 and 3 demonstrated Stenotrophomonas maltophilia and methicillin-resistant Staphylococcus aureus in the blood and nasopharyngeal culture, respectively. Correspondingly, the same organism was cultured from vitreous in Patients 2 and 3. The visual acuity at the last follow-up in Patients 1 to 3 was 20/100, 20/80, and 20/40, respectively. The probable source of infection was identified in each as renal calculi, dental caries, and the pharynx, respectively. Real-time polymerase chain reaction demonstrated the presence of Severe Acute Respiratory Syndrome Coronavirus 2 in the vitreous fluid of Patient 1. Conclusion: We report good outcomes of early intervention for endogenous endophthalmitis in the setting of COVID-19 infection. We also document the presence of SARS-CoV-2 in vitreous. Abstract : This short case series looks at whether the SARS-CoV-2 can be detected in vitreous fluid and the outcomes of endogenous endophthalmitis in patients receiving care for COVID-19 infection.